Virtual Technologies 2008
DOI: 10.4018/978-1-59904-955-7.ch083
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations that Virtual Teams Make so that Complex Tasks Can Be Performed Using Simple E-Collaboration Technologies

Abstract: Using the theoretical lens of compensatory adaptation theory, this study examines how organizational problem-solving teams adapt to lean media and effectively communicate. We examined several successful virtual teams using a bulletin board as their primary communication medium to perform complex process improvement tasks in their natural business environment. Although some established theories predict failure using lean media, savings from use of simple e-collaboration technologies provide motivation for condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Media naturalness theory (Kock 2004(Kock , 2005 is an evolutionary theory that was developed to address theoretical problems with media richness theory, which were brought to light by many focused empirical tests. One of those problems is that there is solid evidence that electronic media that suppress face-to-face communication elements do seem to pose communication obstacles in equivocal team tasks (DeLuca et al 2006;Graetz et al 1998;Kahai and Cooper 2003;Simon 2006). This finding may be seen as supporting media richness theory.…”
Section: Media Naturalness Theorymentioning
confidence: 92%
See 2 more Smart Citations
“…Media naturalness theory (Kock 2004(Kock , 2005 is an evolutionary theory that was developed to address theoretical problems with media richness theory, which were brought to light by many focused empirical tests. One of those problems is that there is solid evidence that electronic media that suppress face-to-face communication elements do seem to pose communication obstacles in equivocal team tasks (DeLuca et al 2006;Graetz et al 1998;Kahai and Cooper 2003;Simon 2006). This finding may be seen as supporting media richness theory.…”
Section: Media Naturalness Theorymentioning
confidence: 92%
“…Again using an object-oriented analogy, this precondition is equivalent to saying that evolutionary and nonevolutionary theories should refer to the same technology class, even though either theory may refer to a subclass of the technology. In information systems investigations, technology-related attributes such as the naturalness of an asynchronous electronic collaboration technology, are often included in causal models as independent constructs (DeLuca et al 2006;Simon 2006). Therefore, without this precondition being satisfied, it could be difficult to identify technology-related constructs that could serve as independent constructs in a causal model depicting the complete theoretical framework.…”
Section: Integrating Evolutionary and Non-evolutionary Theories: Fourmentioning
confidence: 99%
See 1 more Smart Citation
“…This stream includes social influence theory (Fulk et al 1990) and the critical mass theory of interactive media (Markus 1990). Although results regarding social influence on medium choice have been mixed (Kraut et al 1998), this view is found to complement the others in our understanding of medium choice (DeLuca et al 2006).…”
Section: < Insertmentioning
confidence: 93%
“…This theory postulates that team members adapt communication styles based on the richness or naturalness of the medium, compensating for a lack of cues. DeLuca et al . (2006) provide empirical support for this theory, finding that complex tasks can indeed be performed by virtual teams using less rich communication technologies.…”
Section: Considerationsmentioning
confidence: 99%